Recipe for disaster! eaudiobook - Angleberger, Tom (Didi Dodo, Future Spy, 2019)
In this series opener, Koko Dodo the cookie chef has a big problem. Today is the day of the royal cookie contest, and someone has stolen his top-secret fudge sauce! Luckily, a spy enters the scene just in time (or rather, crashes in on her roller skates): Didi Dodo! This might be Didi's first case ever, but she has a daring plan to help Koko. Koko would prefer a safe, simple, sure-to-work plan, but without another option, he and the amateur sleuth take off on a wacky caper full of high-speed chases and big belly laughs that could only come from the mind of the inimitable Tom Angleberger. Each book in the series will focus on a food-related mystery.